Innovative educators in the digital age: Analyzing the impact of school support, self-efficacy, and technology anxiety on teaching creativity - Mulyoto, Mulyoto; Rugaiyah, Rugaiyah; Susanto, Teguh Trianung Djoko (Edelweiss Applied Science and Technology, 2024)
Rapid technological advancements require educators to integrate technology into the learning process, but obstacles such as anxiety about technology often hinder their creativity. This study aims to examine the influence of school innovation climate, technology self-efficacy (TSE), and technology anxiety (TAS) on the creativity of educators in Indonesia, as well as the mediating role of TAS in this relationship. The research method used is a quantitative approach with a cross-sectional survey design involving 248 educator respondents from nine National Police education centers. Data were collected through questionnaires and analyzed by structural equation modeling (SEM). The findings show that the school innovation climate has a positive effect on educators’ creativity, which TSE mediates. In contrast, technology anxiety (TAS) acts as an inhibitor of creativity, with a negative influence on the use of technology in learning. Organizational incentives also have a positive effect on TSE but increase TAS, which ultimately reduces educator creativity. The study recommends giving educators greater work autonomy as well as ongoing technology training to improve TSE and reduce anxiety about technology. The implication of this study is the importance of creating a school environment that supports innovation, as well as designing incentive policies that do not burden educators psychologically. The weakness of this study is the limitation of the convenience sample selection, which affects the generalization of the findings. Future research is suggested to expand the sample with more representative sampling methods and deepen the study of other psychological factors that affect the use of technology in education.